2020
DOI: 10.1177/0146167220977706
|View full text |Cite
|
Sign up to set email alerts
|

Illusory-Correlation Effects on Implicit and Explicit Evaluation

Abstract: Research suggests that people sometimes perceive a relationship between stimuli when no such relationship exists (i.e., illusory correlation). Illusory-correlation effects are thought to play a central role in the formation of stereotypes and evaluations of minority versus majority groups, often leading to less favorable impressions of minorities. Extant theories differ in terms of whether they attribute illusory-correlation effects to processes operating during learning (belief formation) or measurement (beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…More generally, Experiments 6 and 7 are of the very few instances of impression formation research that found, with more than one indirect measure, a discrepancy between self-reported and indirect measured evaluation (see also Van Dessel et al, 2020;and Moran & Bar-Anan, 2013, which was later challenged by Bading et al, 2020). As such, further research could use the paradigm of these experiments for improving the understanding of automatic evaluation and its supposed measures.…”
Section: Implications For the Study Of Indirect Measures Of Judgmentmentioning
confidence: 99%
“…More generally, Experiments 6 and 7 are of the very few instances of impression formation research that found, with more than one indirect measure, a discrepancy between self-reported and indirect measured evaluation (see also Van Dessel et al, 2020;and Moran & Bar-Anan, 2013, which was later challenged by Bading et al, 2020). As such, further research could use the paradigm of these experiments for improving the understanding of automatic evaluation and its supposed measures.…”
Section: Implications For the Study Of Indirect Measures Of Judgmentmentioning
confidence: 99%